2022
DOI: 10.1057/s41288-022-00272-8
|View full text |Cite
|
Sign up to set email alerts
|

Threshold effect for the life insurance industry: evidence from OECD countries

Abstract: We investigate the impact of new financial and economic determinants on life insurance demand for 29 OECD countries for the period 2005–2017 while controlling for a set of widely used socio-demographic and economic characteristics. Based on a panel smooth transition regression model, we find a regime-switching effect characterising the impact of bank concentration and interest rate on the size of the life insurance market, in light of the old-age dependency ratio as the threshold variable. We also show that li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
3
2
0
Order By: Relevance
“…When using the entire sample (OECD + ASEAN), the logarithm of GDP consistently shows a positive and significant impact on all dependent variables, except for the premiums in the life insurance segment when using the total and ASEAN sample. These results are consistent with the static results obtained and previous studies (among others: Dragos (2014) and Dragotă et al (2023)). Additionally, the estimation results also indicate that the lag of two previous periods has a significant impact on gross premiums, suggesting that insurance companies need to anticipate the lasting and persistent effects of the change in income.…”
Section: Dynamic Impactsupporting
confidence: 94%
See 2 more Smart Citations
“…When using the entire sample (OECD + ASEAN), the logarithm of GDP consistently shows a positive and significant impact on all dependent variables, except for the premiums in the life insurance segment when using the total and ASEAN sample. These results are consistent with the static results obtained and previous studies (among others: Dragos (2014) and Dragotă et al (2023)). Additionally, the estimation results also indicate that the lag of two previous periods has a significant impact on gross premiums, suggesting that insurance companies need to anticipate the lasting and persistent effects of the change in income.…”
Section: Dynamic Impactsupporting
confidence: 94%
“…Regarding the first indicator, real GDP, the estimation results indicate a positive and significant relationship with both total and non-life gross premiums. These findings are consistent with previous studies that suggest an increase in income can enhance consumer affordability, leading to higher consumption of insurance products and premiums (Fortune, 1973;Dragotă et al, 2023). However, the results show a positive but insignificant relationship for the life insurance sector.…”
Section: Empirical Findings Static Impactsupporting
confidence: 92%
See 1 more Smart Citation
“…Beck and Webb [2002] and Feyen et al [2011] point out several reasons for the significant and positive correlation between income and life insurance demand: greater availability of life insurance products, a stronger need to protect the potential income of the insured and the expected consumption of dependents, as well as reduced unit cost of larger life policies. Dragota et al [2022] revealed postitive and statistically significant impact of income (GDP per capita) on the demand for life insurance products. Mare et al [2019] considered the impact of employment on the purchase of life insurance and they obtained results showing that there was a significant and positive relationship between employment and life insurance demand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the postulations is that the age demographic of a population affects the insurance industry. On the other hand, a supply-side analysis considers the insurer's perspective and identifies factors such as affordability of premiums, Regulations on prices, claims processing procedures, supply paths, and products regulations as having a significant impact on insurance adoption (Dragotă et al, 2022;Mutembei, 2022;Mwongela, 2022;Sibiko & Qaim, 2020). Under supply side factors such as earnings and profitability, reinsurance and actuarial issues, capital adequacy, liquidity, asset quality, and management soundness impact financial soundness of insurers and indirectly supply of the products (Salameh, 2022).…”
Section: Drivers Of Insurancementioning
confidence: 99%